Assessment of Step and Touch Voltages for Different Multilayer Soil Models of Complex Grounding Grid - Srete Nikolovski; Goran Knežević; Zoran Baus (Institute of Advanced Engineering and Science, 2016)
In this paper the influence of different soil models on step and touch voltages are presented. Soil resistivity is the basic characteristic of soil which affects a number of parameters (temperature, humidity, salt content). Basic methods of measuring soil resistivity presented in this paper are: Wenner method, Schlumberger method, General method, Driven rod (3-probe) method and the Dipole-Dipole method. Soil resistivity measurements are used to obtain an equivalent soil model (uniform model, two-layer horizontal model, multi-layer horizontal model, vertical model and others). The CDEGS software package is used for computing GPR (Ground Potential Rise), touch and step voltage with several different soil models. The resulting effect of soil models on the grounding resistance, GPR at the surface, touch and step voltages are shown. The 3D spatial distribution and 2D presentation of all characteristic values for safety analysis are presented and plotted.